2008
DOI: 10.1098/rspb.2007.1442
|View full text |Cite
|
Sign up to set email alerts
|

Integrating genetic and epidemiological data to determine transmission pathways of foot-and-mouth disease virus

Abstract: Estimating detailed transmission trees that reflect the relationships between infected individuals or populations during a disease outbreak often provides valuable insights into both the nature of disease transmission and the overall dynamics of the underlying epidemiological process. These trees may be based on epidemiological data that relate to the timing of infection and infectiousness, or genetic data that show the genetic relatedness of pathogens isolated from infected individuals. Genetic data are becom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
225
1
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 153 publications
(229 citation statements)
references
References 26 publications
1
225
1
1
Order By: Relevance
“…One result from this study was that the projected most probable infection pathways were between farms that were located in closer proximity than expected by chance [8]. However, distances between farms were not explicitly a part of the FMDV model.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…One result from this study was that the projected most probable infection pathways were between farms that were located in closer proximity than expected by chance [8]. However, distances between farms were not explicitly a part of the FMDV model.…”
Section: Introductionmentioning
confidence: 86%
“…Phylogeographic methods have, for example, been used to trace the global spread of avian influenza over the last decade [7], as well as fine-scale local transmission pathways for the foot-and-mouth disease virus (FMDV) in the UK [8].…”
Section: Introductionmentioning
confidence: 99%
“…The VP1 coding region sequence has been widely used to yield this information as well as for inferring the epidemiological dynamics of the disease such as tracing the origins of outbreaks (e.g. Bastos et al, 2003;Cottam et al, 2008;Knowles and Samuel, 2003;Sangula et al, 2010a;ValdazoGonzález et al, 2011). Hence, a large number of such sequences are available in databases.…”
Section: Introductionmentioning
confidence: 99%
“…Characterization of FMDV evolution is often accomplished by phylogenetic analysis of the VP1 capsid gene/protein, which allows for the distinction of lineages within serotypes (Knowles and Samuel, 2003). Sequencing of FMDV VP1 region and clustering into lineages can be associated with a specific temporal and geographical distribution, from which the potential sources of infection may be traced out and epidemiological trends can be characterized (Cottam et al, 2008 Severe drooling of saliva and vesicular lesions in the mouth parts was observed in affected mithun (Fig 1) and erosive lesions with blanched appearance in the tongue and lower dental pad was found in affected yak (Fig 2). These typical clinical signs/lesions of acute FMD have earlier been reported by Arzt et al (2011) with variable severity depending on the causative strain and host species involved (Grubman and Baxt, 2004).…”
Section: Resultsmentioning
confidence: 99%